2015
DOI: 10.1136/jnnp-2015-310305
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive function poststroke: a review of definition and assessment

Abstract: Metacognition is the conscious knowledge individuals have about their own cognitive capacities and the regulation of these activities through self-monitoring. The aim of this review was to identify the definitions and assessment tools used to examine metacognition in relation to stroke studies. A computer database search was conducted using MEDLINE, CINAHL, PsycINFO, Cochrane Reviews, Scopus and Web of Science. A total of 1412 publications were retrieved from the initial database search. Following the removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 69 publications
0
26
0
1
Order By: Relevance
“…A possible shortcoming of this method is the inaccuracy of the relevant other to assess the behavioural problems of the patient (Maclean, Pound, Wolfe, & Rudd, 2000;Sherer, Hart, & Nick, 2003). However, comparison of the patient's self-rating with that of relevant others is the most commonly used approach to measure self-awareness after stroke (Al Banna, Redha, Abdulla, Nair, & Donnellan, 2016;Leung & Liu, 2011) and…”
Section: Discussionmentioning
confidence: 99%
“…A possible shortcoming of this method is the inaccuracy of the relevant other to assess the behavioural problems of the patient (Maclean, Pound, Wolfe, & Rudd, 2000;Sherer, Hart, & Nick, 2003). However, comparison of the patient's self-rating with that of relevant others is the most commonly used approach to measure self-awareness after stroke (Al Banna, Redha, Abdulla, Nair, & Donnellan, 2016;Leung & Liu, 2011) and…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of the ISA literature have indicated that the Patient Competency Rating Scale and the Awareness Questionnaire are the most commonly used and best validated discrepancy measures of ISA (Smeets et al, 2012;Al Banna et al, 2016). Prigatano et al (1986) developed the Patient Competency Rating Scale (PCRS) as a guide to the clinical interview with patients.…”
Section: The Measurement Of Isa After Tbimentioning
confidence: 99%
“…Metacognition is defined as the higher order thinking involved in overseeing and regulating cognitive processes (Livingston, 2003). Major components of metacognition include self-awareness, self-regulation, and self-monitoring (Al Banna, Redha, Abdulla, Nair, & Donnellan, 2016). The ability to remember effectively in everyday life is dependent on metacognitive factors, including the ability to monitor ongoing performance, predict what amount of information can be remembered, and knowing when to use memory aids (Knight, Harnett, & Titov, 2005).…”
mentioning
confidence: 99%